Pengaruh Harmonisa Pada Gardu Trafo Tiang Daya 100 kVA di PLN APJ Surabaya Selatan - Sentosa Setiadji1, Julius; Machmudsyah, Tabrani; Cipta Wijaya3, Yohanes (Institute of Research and Community Outreach, 2007)
Increasing in Information Technology also increase the use of computer and printer at home. On other hand the energy crisis causing